Video Game Modification in South Africa - Wrensch, Jesse J.; Koornhof, Pieter G.J. (South African Intellectual Property Law Journal, 2017)
This article explores the extent to which the practice of video game modification (commonly referred to as modding) is regulated under South African law. The relevant copyright laws (including impending changes to such laws) are explored, along with practical considerations such as the impact of end-user licence agreements. This is then compared to the position in the USA. The authors argue that modding is likely lawful under South Africa, and that steps should be taken to offer more clarity for modders in the future.
Keywords: 1-Jeux vidéo; 4-Afrique (lieu de production du savoir); _Nettoyé